A criterion for the solvability of A linear boundary-value problem for A system of the second order - Shovkoplyas, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We obtain necessary and sufficient conditions for the solvability of a two-point boundary-value problem for systems of linear differential equations of the second order in the critical case where the corresponding homogeneous boundary-value problem has nontrivial solutions. We construct the general solution of the considered boundary-value problem.